Sistem Pendukung Keputusan Penentuan Prioritas Perbaikan Jalan Menggunakan Metode AHP-TOPSIS (Studi Kasus: Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Ponorogo) - Firdaus Rahman; Muhammad Tanzil Furqon; Nurudin Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Road infrastructure has an important role in supporting the economic, social and cultural sectors. Approximately 49.12% of the total district road length in 2013 is included in the good category, 24.16% included in the medium category, slightly damaged 16.64% and heavily damaged 10.08%. The strategic target of the Directorate General of Highways is the stability of the road area reaches 70%. In the implementation of road improvements by the Office of Public Works and Spatial Planning of the Ponorogo District, it is necessary to consult the priority of road improvement. Modifying road priority priority with AHP (Analytical Hierarchy Process) method - TOPSIS (Preferential Technique with Equalization with Ideal Solution) combines several interrelated factors in road improvement process including: good road conditions, road conditions, defective road conditions, road conditions severely damaged, daily traffic, access, secrets of segments and regent policies. From this study. The low level of system required in the case of there are still some individual interests so there is still mismatch target in the implementation of existing roads.